Effects of dietary lipid levels on growth, antioxidant capacity, intestinal and liver structure of juvenile giant salamander (Andrias davidianus) - Yan, Xiaolu; Pan, Lingcheng; Yu, Junqi; Wang, Shuang; Li, Yong; Zhao, Min; Zhai, Xuliang; Xue, Yang; Luo, Li (Frontiers in Marine Science, 2024)
This research was to assess how varying dietary lipid levels influence the growth, body composition, antioxidant capacity of the liver, and the structure of liver and intestine in A. davidianus. The juvenile A. davidianus (initial weight of 34.20±0.27g) were given isonitrogenous diets (crude protein 57%) that contained six different levels of lipid (5.02%, 8.96%, 12.90%, 16.21%, 19.46%, and 22.80%, respectively) for 105 days. The results revealed that WGR, SGR, PRR and muscle RNA/DNA ratio were significantly enhanced by dietary lipid level up to 16.21%, beyond which these parameters declined; FCR exhibited an inverse trend(P<0.05). The maximum activity of intestinal digestive enzymes and superoxide dismutase (SOD) were observed at the 16.21% dietary lipid level, accompanied by a significant reduction in liver malondialdehyde (MDA) concentration (P<0.05). With the increase in dietary lipid level, the lipid content of both the whole body and liver, along with skin collagen content, initially improved before subsequently declining(P<0.05). At the 16.21% dietary lipid level, the height, number, and width of intestinal mucosal folds significantly increase (P<0.05), and intestinal microvilli were more orderly arranged. At the 22.80% dietary lipid level, the liver cells exhibited degradation of the cell membrane, alongside an increased presence of autophagosomes; additionally, the mitochondria demonstrated significant swelling and rounding. Optimal lipid level could enhance feed utilization efficiency and promote both intestinal and liver health in A. davidianus. In contrast, high dietary lipid level has a detrimental effect on the health of A. davidianus. According to WGR, skin collagen content, muscle RNA/DNA ratio, total cholesterol (TCHO) and lipase activity, it has been determined through quadratic curve model analysis that the optimal dietary lipid level for juvenile A. davidianus ranges from 13.3% to 17.5%.